(untitled) (Research, Society and Development, 2022)
Introduction: In the hospital environment, the clinical pharmacist’s conduct consists of optimizing pharmacotherapy, promoting the rational use of medications, and always seeking to improve the quality of life of users, preventing significant drug interactions. The performance of clinical-hospital activities by the pharmacist is currently expanding, as professionals are able to play their role in an advantageous way, both for patients and for the care units. Thus, the present study aims to describe the impact of activities carried out by pharmacists and highlight the main results obtained from their insertion as a professional member of a multidisciplinary team in hospital units. Methodology: The evident study is a bibliographic research of the integrative review type. Results and discussions: In total, through the use of keywords in the databases, 108,070 articles were found. After using the filters, these specified by the inclusion and exclusion criteria, a total of 12 articles remained to be commented on in this text. Final considerations: The role of the pharmacist in the hospital environment is of fundamental importance to guarantee the maintenance of the health of inpatients. It is observed that the clinical activities performed by this professional are considerably capable of reducing damage associated with the misuse of medications. Therefore, the pharmacist is responsible for ensuring that drug therapy occurs effectively and safely, given the individualities of each subject.